Contrastive Analysis of British and American English in Relation To Teaching English as a Foreign Language - Novalina Sembiring (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This research was a descriptive research which was aimed at finding out the similarities, dissimilarities and the contributions of the contrastive analysis on teaching English as a foreign language. The data of this research were collected through library and internet sources. The researchers use comparative descriptive method to analyse the data. The obtained results was the comparison of American and British English in vocabulary, grammar, spelling, pronunciation and the contributions of them in teaching English as a foreign language. The research finding shows that British and American English are very similar in many aspects. Even though British and American English are mostly similar, they also have some differences. The difference of British and American English can be found in terms of vocabulary, grammar, spelling and pronunciation. Among them, vocabulary is the largest one. It is suggested that lecturers and teachers aware of the similarities and differences between British and American English in teaching English as a foreign language so that it will lead to the successful teaching of English including its varieties.